"Don't Do as I Do"—The US Response to Russian and Chinese Cyber Espionage and Public International Law. Issue 3 (1st June 2018) - Terry, Patrick C. R.
Abstract : The Russian government is accused of hacking emails circulating among senior members of Hilary Clinton's campaign team to support President Trump's election in 2016. This was not the first time the United States was the target of massive cyber espionage: The Chinese government is believed to have gained sensitive information on 22.1 million US government employees through "cyber intrusions" in 2014. This Article will examine whether cyber espionage of this kind is unlawful under public international law and will conclude that it is. Specifically, such espionage can result in a violation of territorial sovereignty and will likely violate the principle of non-intervention in the internal affairs of other States. Yet, based on the controversial "clean-hands-doctrine, " past US actions in the realms of cyber espionage and intervention may well invalidate any claims it asserts against Russia or China.